Reference values of lead in blood and related factors among Korean adolescents: the Korean National Health and Nutrition Examination Survey 2010-2013 - Min-Gyu Choi; Mi-Jung Park; Shin-Hye Kim (Korean Pediatric Society, 2016)
PurposeThis study aimed to assess the reference values and factors influencing blood lead levels among Korean adolescents.MethodsThe study population consisted of 1,585 adolescents (801 males, 784 females; aged 10-19 years) who participated in the Korea National Health and Nutrition Examination Survey 2010-2013. We analyzed blood lead concentrations in relation to demographic/lifestyle characteristics for all participants. "Reference values" of blood lead levels were calculated as the upper limit of the 95% confidence interval of the 95th percentile.ResultsThe average "reference value" for blood lead concentrations among Korean adolescents was 2.25 µg/dL (2.49 µg/dL for males, 2.07 µg/dL for females), and the geometric mean of the blood lead concentrations was 1.34 µg/dL. Males had higher blood lead concentrations than females (male, 1.48 µg/dL; female, 1.19 µg/dL; P<0.001). Elementary school students had higher blood lead concentrations than junior and senior high school students (1.44 µg/dL vs. 1.31 µg/dL, P<0.001). Participants living in detached houses had higher blood lead concentrations than those living in apartments (P<0.001) and current smokers had higher concentrations than nonsmokers or participants with secondhand smoke exposure (P<0.05). Additionally, participants with excessive alcohol consumption had higher levels than non-drinkers (P<0.001).ConclusionThis study provides national reference data on blood lead concentrations stratified by demographic and lifestyle factors among Korean adolescents. Further studies are needed to elucidate the relationship between increased lead exposure and demographic factors including type of housing.